Reading and planning with the landscape: a study in the Água Comprida basin in Bauru-SP - Mattos , Karina Andrade; Foloni, Fernanda Moço (Revista Nacional de Gerenciamento de Cidades, 2022)
Observing the strictly functional urban planning process of contemporary cities, the present work proposes, through the study of a cutout in the watershed of the Água Comprida stream in Bauru-SP, to analyze the relationship between clear and constructed spaces along the watercourse. For this, it was sought in the legislation, in the historical context, in the related bibliographies and in the perception of space, to understand how this process of rupture occurred between the built and the natural, between man and nature, which generated an urban space disconnected from the green areas. Therefore, it seeks to explore how landscape architecture can help in understanding and planning the landscape of cities as a unit, bringing together economic, sociocultural and environmental processes.